2010
DOI: 10.1073/pnas.0904532106
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of amyloid plaque formation suggests an intracellular basis of Aβ pathogenicity

Abstract: The formation of extracellular amyloid plaques is a common patho-biochemical event underlying several debilitating human conditions, including Alzheimer’s disease (AD). Considerable evidence implies that AD damage arises primarily from small oligomeric amyloid forms of Aβ peptide, but the precise mechanism of pathogenicity remains to be established. Using a cell culture system that reproducibly leads to the formation of Alzheimer’s Aβ amyloid plaques, we show here that the formation of a single amyloid plaque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
230
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(242 citation statements)
references
References 63 publications
11
230
0
1
Order By: Relevance
“…This is supported by some recent reports demonstrating that A␤ in culture medium is internalized and aggregated intracellularly into fibrils, eventually causing membrane disruption (47,48). Further studies are required to dissect the structural and molecular mechanisms underlying the critical role of protofibril-monomer interactions in A␤ toxicity.…”
Section: Discussionmentioning
confidence: 62%
“…This is supported by some recent reports demonstrating that A␤ in culture medium is internalized and aggregated intracellularly into fibrils, eventually causing membrane disruption (47,48). Further studies are required to dissect the structural and molecular mechanisms underlying the critical role of protofibril-monomer interactions in A␤ toxicity.…”
Section: Discussionmentioning
confidence: 62%
“…Electron micrographs of a sample of MSP3F on the 1st day showed the presence of homogeneous spherical structures that were similar to the self-assemblies (amylospheroid) and intermediate species formed by A␤-derived diffusible ligands (32,34). At 50 h, these spherical structures were primarily transformed to short fibrillar assemblies resembling intermediate species formed during amyloidogenesis of A␤ peptide (35), whereas at 72 h clear amyloid fibrils were noticeable along with few amorphous aggregates. The role of amorphous aggregates has been studied in detail in a kinetic study of a prion protein-based peptide in which the aggregates were shown to have a dual role for releasing monomeric species as well as to act as a site for initiation of amyloid growth (36).…”
Section: Discussionmentioning
confidence: 94%
“…The aggregation of ␤-amyloid (A␤) peptide as extracellular amyloid deposits on the cholesterol-rich regions of neuronal membrane is the primary feature of AD (1,2). Recent evidences showed that A␤ peptide is generated extracellularly and intracellularly by the enzymatic breakdown of the amyloid precursor protein by ␤-and ␥-secretases.…”
mentioning
confidence: 99%